ANALISIS TUMBUH SELADA (LACTUCA SATIVA L) PADA PERBEDAAN JENIS PUPUK ORGANIK CAIR ( Lettuce (Lactuca Sativa L) Growth Analysis At Different Type Of Liquid Organic Fertilizer) - Made Deviani Duaja; . Arzita; Yan Redo (Bioplantae, 2012)
The objectives of this research are to analysis the growth and yield of Lettuce (Lactuca sativa L) at different type of organic liquid fertilizers. The experiment has conducted at Agriculture Faculty Research Farm, Jambi University. Six treatments were arranged in Randomized Completed Block Design. The treatments are kinds of liquid organic fertilizers, they are P0 (none of liquid organic fertilizers), P1 (Golden Harvest liquid organic fertilizers), P2 (NASA liquid organic fertilizers), P3 (Compost Tea liquid organic fertilizers), P4 (Nutrisi Saputra liquid organic fertilizers), P5 (Bio Subur liquid organic fertilizers), and P6 (Alam Natural I liquid organic fertilizers). The result shows that there is significant effect of liquid organic fertilizers to every parameter of growth analysis: average leaf area index, average net assimilation rate and average plant growth rate. The trend of growth parameter indicated that Golden Harvest always achieved the highest. The highest lettuce yield was achieved at Golden Harvest liquid organic fertilizers, but there are no significant differences effect between Golden Harvest and Bio Subur.Key words : Lettuce, growth, yield, liquid